Evaluating the Flame Retardancy of Shaving Super Bamboo Layer by Layer Self-Assembly With Phytic Acid-Polyethyleneimine - Lin, Peng; Jiang, Yingqiu; Ru, Xiaolin; Che, Wenbo; Zhang, Xiaochun; Ma, Lingfei; Hou, Junfeng; Yu, Youming (Frontiers in Materials, 2021)
To improve the flame retardancy of bamboo materials, layer by layer (LbL) self-assembly with phytic acid (PA)-polyethyleneimine (PEI) on the surface of shaving super bamboo specimens with different solution concentrations of PA-PEI and times of LbL self-assembly was completed in this study. Results of Fourier transform infrared analysis showed that PEI was well assembled to the surface of bamboo specimens by hydrogen bond with PA as intermediation. Application of PA and PEI significantly promoted the formation of carbon residue as illustrated in the simultaneous thermal measurements. Specifically, the peak heat release rate of bamboo specimens self-assembled with 10 wt.% PA and 10 wt.% PEI solution for 5 times was 19.36% smaller and total heat release was 22.30% smaller than the control in a cone calorimeter analysis. The treated bamboo specimen showed increases of 35.56% and 480.70% in fire performance index and residual mass, respectively, compared to the control. Besides, yields of CO and CO2 were decreased by 17.77% and 17.07% in comparison with the control, respectively. LbL self-assembly with PA-PEI promoted the generation of residual char layer with excellent stability, can effectively improve the flame retardancy of bamboo materials.